Distribution state estimation for smart distribution system - Karimi, M.; Mokhlis, Hazlie; Bakar, Ab Halim Abu; Shahriari, A. (2013)
With the penetration of distributed generations into distribution network, more distribution automation will be required. Therefore, smart grid technologies become more important aspect in electric power system. Real-time monitoring of the network is a main step to achieve smart grid technologies. Hence, distribution state estimation becomes more essential for real-time monitoring of traditional distribution network. This paper addresses a distribution state estimation method to achieve smart grid technologies in a traditional distribution network. It will involve exploring distribution state estimation method with minimum number of real-time measurement devices. Therefore, pseudo measurements are applied to address the limitation of the number of real-time measurements. In addition, by incorporating load model, state estimation results are improved and enhanced. In this paper, dynamic aspect of distribution state estimation has been developed for smart grid purposes. The proposed distribution state estimation results are justified with PSCAD/EMTDC software to verify and validate the system state variables.